Business policy and strategy - Ilano, A.B. (Quezon City, Philippines : Rex Printing Company, Inc., 2017)
This textbook is about business policy and strategic management, two elements that can be best be appreciated from the top of an organization.
Chapter 1. Strategy: Defined Chapter 2. The Organization Chapter 3. The Environment Chapter 4. Creating Value at the business level Chapter 5. Competitive Strategy Chapter 6. Corporate Level strategy Chapter 7. Transformation and growth
Includes bibliographical references and index.
Keywords: STRATEGIC PLANNING